The History of the Bargut Confrontation in Northeastern China (early 20th century): Ethno-Political and Religious Aspects (based on archival materials) - Bair Ts. Gomboev; Eduard V. Batunaev (Монголоведение)
Introduction. The article is devoted to the study of the history of the confrontation of the Barguts in Manchuria in the context of historical events in China. On the territory of Barga, in northeastern China, the socio-political situation at the beginning of the 20th century was difficult, caused not only by internal political processes of sharing power (confrontation of ethnic groups, preservation of traditional types of nature management), the struggle for resources, but also by external influences for domination and dominance in northeast East Asia (Russia, China and Japan). Under these conditions, the governments of Russia, Japan and the Chinese authorities, taking into account emerging political and international situations, methodically defended their interests in the region. The most affected were the peoples of Barga, in particular, the Barguts, who most advocated sovereignty. The purpose of the article is a comprehensive study of the political situation and ethno cultural aspects to identify the features of the formation of the Bargut ethnic group in the period from 1900 to 1921. Materials and methods. The research methodology is based on comparative historical, historical-genetic, historical-dynamic, retrospective methods, and interviewing methods, which made it possible to most fully analyze the main stages and patterns of the history of the Bargut confrontation in Manchuria in the context of historical events in China, taking into account ethno political and religious aspects. Based on archival materials from the AVPRI, field research, and the achievements of modern domestic and foreign historiography, problematic and key issues regarding a specific ethnic group of the Barguts of northeast China in a certain historical period (1900–1921) are considered. Results. The identification of the ethnic history of the Barguts of northeastern China and the introduction of new archival materials made it possible to identify the features of the national liberation struggle for the sovereignty of the Bargut ethnic group and the search for ways to achieve goals.